Simultaneous realization of holey in-plane defects and expanded interlayers in N-containing nanocarbons from a non-covalent-bonded organic framework for efficient oxygen reduction reaction - Wang, Sumin; Shen, Zhiruo; Wang, Qiguan; Wang, Hong-Yan (Electrochimica acta, 2021)
•An assembly motif of hydrogen-bonded organic frameworks is used to prepare a novel expanded and holey NCM (EH-NCM) with interlayer distance of 0.44 nm.•EH-NCM shows ORR activity with half wave potential of 0.93 V and H2O2 yield of less than 4%, superior to the commercialized Pt/C.•The zinc-air battery (ZAB) based on EH-NCM shows a high capacity and excellent cycled stability, compared with Pt/C-based ZAB.•The theoretical calculation and potentiostatic intermittent titration technique (PITT) proved that the mass transfer is greatly improved in EH-NCM. We herein design a non-covalent assembly motif of hydrogen-bonded organic frameworks (HOF), which is experienced by a simple carbonization process to form a novel both expanded interlayer and holey in-plane nitrogen-containing nanocarbon material (EH-NCM). The escaped species in pyrolysis from the element decomposition in the HOF plays an important role in the simultaneous construction of holey defect and expanded interlayer. The potentiostatic intermittent titration experiment shows that oxygen diffusion coefficient in EH-NCM is improved by 1 order of magnitude compared with the commercial Pt/C and the unexpanded NCM. Calculations also show in-plane defects can efficiently bind with O2 and benefit to four-electron oxygen reduction reaction (ORR) process, assisted by the enlarged interlayer distance. The as-prepared EH-NCM delivers ORR activity with half wave potential and onset potential at 0.93 V and 1.05 V respectively, limited current density of 6.1 mA cm−2, and a low Tafel slope of 67 mV dec−1, showing H2O2 yield of less than 4% superior to the commercialized Pt/C. Also EH-NCM-based Zn–air battery displays excellent cathode performances. The accelerated mass transfer and maximum exposure of the active sites resulted from the holey and expanded dual structure of EH-NCM is responsible for the outstanding ORR performances. A non-covalent assembly motif of hydrogen-bonded organic frameworks is designed to simultaneously realize a novel both expanded and holey defective NCM (EH-NCM). Stimulated by the greatly boosted mass transfer, EH-NCM shows ORR activity with half wave potential of 0.93 V and H2O2 yield of less than 4%, as well as a high capacity and excellent stability for zinc-air battery. [Display omitted]